Outcomes after the Fontan operation in the Middle East: A large Saudi Arabian single centre experience. (15th February 2021) - Al Najashi, Khalid; Farouk, Sameh; Atiyah, Merna; Mohsin, Shazia; Mohamed, Wafa; Saeed, Mossab; Elwi, Ahmed; Veldtman, Gruschen R.
Abstract: Background: Fontan outcomes data from large volume Middle Eastern Centres are lacking. We report our experience after the Fontan operation from a tertiary cardiac centre in Saudi Arabia. Method: All 458 consecutive patients who had Fontan surgery 1986 through 2015 at the Prince Sultan Cardiac Centre, Riyadh [PSCC], Saudi Arabia, were evaluated for baseline, early and late post-operative outcomes and their uni and multivariate determinants. Results: The mean age at Fontan operation was 7 years [IQR 4.8–9.0]. The most common anatomic diagnoses were tricuspid atresia (104 [23%]) and double-inlet left ventricle (81 [18%]). Only 3 patients in the present series had hypoplastic left heart syndrome [HLHS]. Early mortality [i.e. during Fontan surgical admission] was 3.1%. At late follow-, 35 (8%) patients were lost to follow up. The 1, 5, 10, 20 and 30 year survival was 96%, 94%, 93% and 85%, respectively. In the modern surgical era, 5, 10 and 15 year survival were 96%, 95% and 93% respectively. Univariate determinants of death or transplant were hypoalbuminemia, elevated NtProBNP >500, surgical era prior to 1999, the lack of Fontan fenestration, and prior atriopulmonary Fontan [APF] procedure. On multivariate analysis, surgical era before 1999 and prior APF procedure were independently associated with death or transplant. Conclusions: Fontan patients from this large volume Middle Eastern centre have comparable early and late mortality outcomes compared to prior published reports. Rigorous selection criteria at the time of Fontan, and Fontan specific dedicated care teams are likely contributors to this success. Highlights: This large volume single centre outcomes analysis, of univentricular physiology patients with a Fontan operation, is the first of its kind from the Middle East. It demonstrates excellent late outcomes with 93% late survival at 10 years, 89% at 20 years and 85% at 25 years follow up, and a low rate of loss to follow up of only 8%. We attribute such encouraging outcomes to rigorous patient selection at the time of Fontan and dedicated teams to ensure good inpatient as well as outpatient management with follow-up.